2016
DOI: 10.18632/oncotarget.9135
|View full text |Cite
|
Sign up to set email alerts
|

miR-592/WSB1/HIF-1α axis inhibits glycolytic metabolism to decrease hepatocellular carcinoma growth

Abstract: Hepatocellular carcinoma (HCC) cells rapidly switch their energy source from oxidative phosphorylation to glycolytic metabolism in order to efficiently proliferate. However, the molecular mechanisms responsible for this switch remain unclear. In this study, we found that miR-592 was frequently downregulated in human HCC tissues and cell lines, and its downregulation was closely correlated with aggressive clinicopathological features and poor prognosis of HCC patients. Overexpression of miR-592 inhibited aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…4,5 The AKT pathway and hypoxiainducible factor 1 (HIF-1) are major signaling cascade that regulates glucose metabolism as well as controls cellular growth. 6,7 They could enhance glucose transporter gene expression, increase phosphofructokinase activity, and stimulate the glucose to lactate metabolic pathway, 8,9 AKT mainly enhances hexokinase II (HKII) gene expression, thus promoting glucose capture. 10 MicroRNAs (miRNAs) are single-stranded, small noncoding RNAs with 18-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The AKT pathway and hypoxiainducible factor 1 (HIF-1) are major signaling cascade that regulates glucose metabolism as well as controls cellular growth. 6,7 They could enhance glucose transporter gene expression, increase phosphofructokinase activity, and stimulate the glucose to lactate metabolic pathway, 8,9 AKT mainly enhances hexokinase II (HKII) gene expression, thus promoting glucose capture. 10 MicroRNAs (miRNAs) are single-stranded, small noncoding RNAs with 18-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of HIF-1α is a critical factor in its action on relevant gene expression, and WD repeat and SOCS box containing 1 (WSB1) has been reported to enhance the HIF-1α protein stability derived from the abnormally low expression of miR-592 in hepatocellular carcinoma cells with enhanced glycolysis and proliferation [144]. In osteosarcoma cells, which have a high energy demand but low ATP-generating efficiency, increasing miR-543 targets the 3'-UTR of protein arginine methyltransferase 9 (PRMT9) to decrease PRMT9-induced HIF-1α instability; thereafter, elevated HIF-1α boosts glycolysis and proliferation of osteosarcoma cells [145].…”
Section: Posttranslational Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…In pancreatic cancer, the expression of miR-646 [181] and miR-548 [67] is correlated with clinicopathological indicators such as TNM stage and overall survival (OS), and hypoxia-induced lncRNA NUTF2P3-001 overexpression also indicates advanced TNM stage and shorter survival time of patients [88]. Both Low expression of miR-592 [144] and high expression of miR-130b [184] can bring about poorer OS in hepatocellular carcinoma patients. For gastric cancer, it has been demonstrated that miR-421 regulated by HIF-1α not only causes longer OS, but also can shorten the time to relapse of patients [185], and lncRNA BC005927 induced by hypoxia is also frequently upregulated in gastric cancer samples, showing adverse effects on a series of prognostic parameters, such as TNM stage, lymph node metastasis, and survival time [81].…”
Section: Perspectives On Hif-1α and Ncrnas In Clinical Practicementioning
confidence: 99%
“…This evidence suggests that hypoxia-induced PIM1 is important for the mitochondrial-glycolytic metabolism shift in HCC. Jia et al (2016) reported that miR-592 was downregulated in HCC specimens. These authors showed that overexpression of miR-592 reduced HIF-1a, glycolytic metabolism, and HCC growth.…”
Section: Alteration Of Glucose Metabolism In Hccmentioning
confidence: 99%